The Music of Interwar Modernism in Slovenia (1918–1927) - Pompe, Gregor (De musica disserenda, 2017)
Analyses of selected works are used to re-examine the stylistic orientation of Slovenian music between the two world wars. The music of composers active in this period exhibits a characteristic ambivalence in which the conflict between new, progressive compositional trends and the aesthetic ideals of the prior century can be seen.